1995
DOI: 10.2118/26074-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Reservoir Compaction and Surface Subsidence at South Belridge

Abstract: Summary Finite-element models of depletion-induced reservoir compaction and surface subsidence have been calibrated with observed subsidence, locations of surface fissures, and regions of subsurface casing damage at South Belridge and used predictively for the evaluation of alternative reservoir-development plans. Pressure maintenance through diatomite waterflooding appears to be a beneficial means of minimizing additional subsidence and fissuring as well as reducing axial-compressive-type ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For example, there is little correlation between shear failure in wells and their position with respect to the outer edge of the field, where the large scale and long term horizontal shear stress is often the greatest. This was also the case for the South Belridge Field to the north, where it was observed that well failures occurred throughout the area of production rather than simply along the perimeter or within the centre of the zone of subsidence (Hansen et al 1995;Myer et al 1996;Fredrich et al 2000). Furthermore, an analysis of the spatial distribution of well failures at the South Belridge field, obtained from a comprehensive database, indicates that well damage is influenced by local patterns of injection and production .…”
Section: Discussionmentioning
confidence: 79%
“…For example, there is little correlation between shear failure in wells and their position with respect to the outer edge of the field, where the large scale and long term horizontal shear stress is often the greatest. This was also the case for the South Belridge Field to the north, where it was observed that well failures occurred throughout the area of production rather than simply along the perimeter or within the centre of the zone of subsidence (Hansen et al 1995;Myer et al 1996;Fredrich et al 2000). Furthermore, an analysis of the spatial distribution of well failures at the South Belridge field, obtained from a comprehensive database, indicates that well damage is influenced by local patterns of injection and production .…”
Section: Discussionmentioning
confidence: 79%
“…The geomechanical finite element simulations of reservoir compaction and surface subsidence at the Belridge Diatomite Field (e.g., Hansen et al, 1995;de Rouffignac et al, 1995;Fredrich et al, 1996Fredrich et al, , 1998 depend fundamentally on: (1) the mechanical loading, which is a direct function of the reservoir pressure history as derived from two-and three-dimensional reservoir simulations; and (2) the material model and constitutive parameters of the reservoir and overburden rock.…”
Section: Resultsmentioning
confidence: 99%
“…The initial stress state & time zero was prescribed following Hansen et alg The vertical (total) principal stress due to gravitational loading was calculated directly on an element by element basis from the bulk density of the overlying materials with initial pore pressures in the different stratigraphic layers calculated as described in Ref. 9. The two effective horizontal principal stresses, that are initially oriented parallel to the model boundaries, were calculated for each element by multiplying the effective vertical stress previously computed by factors of 0.65 and 1.20.…”
Section: Contactmentioning
confidence: 99%
“…The two effective horizontal principal stresses, that are initially oriented parallel to the model boundaries, were calculated for each element by multiplying the effective vertical stress previously computed by factors of 0.65 and 1.20. 9 The model's response to the application of the in siru stresses (referred to as the geostatic step) serves as a quality check. Large inelastic deformations and/or the appearance of shear components in the stress tensor may indicate that the imposed initial stress state is not consistent with the geomechanical model.…”
Section: Contactmentioning
confidence: 99%